2020
DOI: 10.1146/annurev-cancerbio-030419-033619
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein Kinase: Friend or Foe in Cancer?

Abstract: The AMP-activated protein kinase (AMPK) is activated by energy stress and restores homeostasis by switching on catabolism, while switching off cell growth and proliferation. Findings that AMPK acts downstream of the tumor suppressor LKB1 have suggested that AMPK might also suppress tumorigenesis. In mouse models of B and T cell lymphoma in which genetic loss of AMPK occurred before tumor initiation, tumorigenesis was accelerated, confirming that AMPK has tumor-suppressor functions. However, when loss of AMPK i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 85 publications
2
24
0
Order By: Relevance
“…Overall, although AMPK was initially suggested as a tumor suppressor, there is ample evidence that this enzyme could be, instead, a tumor promoter [ 83 , 84 ]. This notion is based on its ability to control the metabolic reprogramming of cancer cells under stress circumstances as those occurring in the tumor microenvironment.…”
Section: Metabolic Changes In Cancer Developmentmentioning
confidence: 99%
“…Overall, although AMPK was initially suggested as a tumor suppressor, there is ample evidence that this enzyme could be, instead, a tumor promoter [ 83 , 84 ]. This notion is based on its ability to control the metabolic reprogramming of cancer cells under stress circumstances as those occurring in the tumor microenvironment.…”
Section: Metabolic Changes In Cancer Developmentmentioning
confidence: 99%
“…In addition, somatic mutations in STK11 are now known to occur quite frequently in non-inherited cancers. For example, the gene is mutated in 10–20% of all cases of human lung cancer [ 1 , 140 , 141 , 142 ].…”
Section: Is Ampk a Tumour Suppressor Or A Tumour Promoter?mentioning
confidence: 99%
“…The cBioPortal database [ 159 , 160 ] provides a user-friendly platform to interrogate genetic changes occurring in human cancers for any particular gene, based on the numerous genomic studies of different cancer types that have been performed. Recent analyses of this database [ 1 , 140 , 161 ] revealed that, while the PRKAA2 gene encoding AMPK-α2 is often mutated in human cancers, the PRKAA1 gene encoding AMPK-α1 (also, interestingly, the PRKAB2 gene encoding AMPK-β2) is often amplified instead. While not providing conclusive proof, these results suggest that, if anything, AMPK-α2 may act as a tumour suppressor in human cancers, while AMPK-α1 (and -β2) are more likely to represent tumour-promoting genes.…”
Section: Is Ampk a Tumour Suppressor Or A Tumour Promoter?mentioning
confidence: 99%
See 2 more Smart Citations